Exploring Students’ Perceptions of YouTube as a Tool to Enhance English Speaking Skills: A Qualitative Study at SMKN 1 Barru - Ridwan, Nuredah; Rauf, Wahyuddin; Chandra, Ade (Jurnal Edukasi Saintifik, 2024)
This study aims to explore students’ perceptions of using YouTube as a learning tool to enhance their English-speaking skills at SMKN 1 Barru. Employing a qualitative case study design, the research involved ten vocational students selected purposively from the eleventh grade. Data were collected through semi-structured interviews and classroom observations, focusing on students’ experiences, challenges, and perceived benefits when using YouTube in English learning. The data were analyzed using a thematic analysis approach, supported by triangulation to ensure validity and credibility. The findings reveal that students perceive YouTube as a compelling, engaging, and accessible platform for improving speaking skills. The use of authentic videos helps learners enrich vocabulary, improve pronunciation, and build speaking confidence through imitation and exposure to native-like models. Moreover, YouTube fosters self-directed learning and motivation by allowing students to control their pace and learning environment. However, several challenges were also noted, such as distraction and limited internet access. The study highlights the pedagogical potential of YouTube in promoting interactive and autonomous learning, particularly in vocational education contexts where communicative competence is essential.